Do welfare and labour market institutions influence unemployment duration of immigrants? Evidence from 11 European countries - Centre d'études de populations, de pauvreté et de politiques socio-économiques, Differdange; Meyer Christensen, Anna; Pavlopoulos, Dimitris (Differdange, 2010)
"This paper investigates the effect of institutions on the unemployment gap between immigrants and natives in 11 EU-countries. We study whether benefits provide disincentive effects as the job-search theory suggests or rather efficiency gains as alternative theories propose. Further than the existing literature, we study unemployment duration instead of unemployment incidence, we distinguish between exits to inactivity, primary and secondary employment and we use individual-level measures for unemployment benefits. We apply a competing-risk event-history model using the ECHP. Our results favour the efficiency-gains argument for granting immigrants benefits as we find that benefits reduce unemployment duration and prevent transitions into inactivity. Employment perspectives of immigrants are better when demand for low-skilled labour is high, employment protection is low and immigration policy is labour-market oriented."